2023
DOI: 10.1172/jci.insight.170181
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal transcriptomics highlight lncRNAs implicated in ulcerative colitis, Crohn’s disease, and celiac disease

Abstract: Ulcerative colitis (UC), Crohn's disease (CD), and celiac disease are prevalent intestinal inflammatory disorders with nonsatisfactory therapeutic interventions. Analyzing patient data-driven cohorts can highlight disease pathways and new targets for interventions. Long noncoding RNAs (lncRNAs) are attractive candidates, since they are readily targetable by RNA therapeutics, show relative cell-specific expression, and play key cellular functions. Uniformly analyzing gut mucosal transcriptomics from 696 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Information about tissue biopsy location, medication, gender, and age were not listed in some datasets. Different tissue locations have been shown to influence lncRNA expression profiles [35,36]; unfortunately, subgrouping by available tissue location would lead to groups that were too small for a robust statistical analysis. Comparison of lncRNA expression between tissue types could lead to erroneous interpretations depicted in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Information about tissue biopsy location, medication, gender, and age were not listed in some datasets. Different tissue locations have been shown to influence lncRNA expression profiles [35,36]; unfortunately, subgrouping by available tissue location would lead to groups that were too small for a robust statistical analysis. Comparison of lncRNA expression between tissue types could lead to erroneous interpretations depicted in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of lncRNA expression between tissue types could lead to erroneous interpretations depicted in Figure 2. A recent review of lncRNA mucosal transcripts implicated in UC, Crohn's disease, and celiac disease revealed that the lncRNAs showed significantly more location-specific expression along the GI tract than the protein-coding genes [36]. Comparing tissue types directly could lead to a more comprehensive set of tissue-specific differentially expressed lncRNAs in UC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other lncRNAs such as LOC339803 or Lnc-UC have been speci cally associated with the development of in ammation in IBD (9,10). Furthermore, a recent transcriptome study of the intestinal mucosa have identi ed several dysregulated lncRNAs, including WAKMAR2, in IBD and celiac disease with a highly tissue-dependent expression patterns (14). Additionally, WAKMAR2 has previously been linked to other in ammatory pathologies as rheumatoid arthritis, psoriasis or chronic dermatitis (26, 29, 30), highlighting the importance of lncRNAs in in ammatory disorders (31).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have demonstrated that some lncRNAs have a more location speci c expression in the GI tract than coding genes, suggesting they may serve as prognostic markers and also as potential targets to improve disease outcome (14). Among these lncRNAs, WAKMAR2, previously related to in ammation in keratinocytes, is present on chromosome 6 (q23.6) and harbors an IBD associated SNP within its sequence (rs5029924) (15).…”
Section: Introductionmentioning
confidence: 99%